Evaluation Model of the Affective Aspect for Religion Education in Madrasah Aliyah and Pondok Pesantren - Tsani, Iskandar (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
The objective of this present research is to develop an evaluation model of the affective aspect of Islamic Religious Education (IRE) in madrasah aliyah and pondok pesantren. It is developmental research with a mixed approach (quantitative and qualitative design) covering three phases of development: pre-development, development, and dissemination. This model consists of (1) a guide for the evaluation model, and (2) the instrument for the evaluation model in the forms of questionnaires, observation sheets, and questionnaires for self-evaluation. The instrument validity of the evaluation model consisting of questionnaires, observation sheets, and questionnaires for self-evaluation was determined by expert judgment while its reliability was decided using the Alpha Cronbach. Instrument validity consisting of questionnaires, observation sheets, and questionnaires of self-evaluation is a construct validity determined using Exploratory Factor Analysis (EFA) and Confirmatory Factor analysis (CFA), while its reliability was decided using Alpha Cronbach. The results showed that the components of the evaluation model of the Affective Aspect for IRE (AEIRE) consist of Input, Process, and Output. All instruments of the model show a good fit. The model is effective enough for madrasahs aliyah and pondok pesantrens. According to the teachers of IRE, the guide for the use of the model is very good.